(untitled) (Mustansiria Dental Journal, 2018)
Background: The establishment of the correct vertical rest position is considered essential, because this position is a critical landmark in determining the vertical relation of occlusion. Unfortunately, the physiologic rest position is variable as it may be influenced by muscle tension, fatigue, and properioception. A study was therefore, undertaken to investigate the repeatability of vertical dimension measurement by different education degree groups. Materials and methods: thirty patients were investigated for vertical dimension measurement by different education degree groups (5th class undergraduate students, house officers dentists, MSc and PhD), depending on a very popular and simple method by using millimeter ruler. Result: the result showed that the difference in the vertical dimension measurements by the four different education degree groups was clinically not significant. Conclusion: 1.The vertical dimension measurements obtained from the undergraduates and house officer dentists were dependable. 2.The time-span of the measuring procedure has no effect on the determination of the vertical dimension throughout a single visit. 3.The caliper method was practical, simple and accurate in academic work. As The result of this study reveals the reproducibility of this method by all of the investigators.